Little engine that could (The) - Piper, Watty (New York : Scholastic Inc, 1976)
The kindness and determination of the Little Blue Engine have inspired millions of children around the world since the story was first published in 1930. Cherished by readers for sixty year, The Little Engine That Could is a classic childhood.
Keywords: Trains--Fiction; Children stories